Review of multiport isolated bidirectional converter interfacing renewable and energy storage systems - Arulmozhi Subramanian; Santha KR (International Journal of Power Electronics and Drive Systems (IJPEDS), 2020)
Multi port converters increasingly gain prominance in the recent past to interface renewable energy sources like photovoltaic cells, fuel cells with the load. Energy storage elements like battery and supercapacitors nd major place as an additional and alternate sources in systems with primary renewable energy sources to overcome its intermittency issues. As these energy storage element's charging and discharging cycles are to be controlled, an isolated bidirectional converter topology with transformer is used. The galvanic isolation provided by the high frequency ac link transformers in partly isolated and fully isolated topologies makes these converters most preferrable in high power applications like electric vehicles. A comprehensive review is performed on various three port partly isolated and fully isolated topologies addressed by dierent research groups. The key contributions on soft switching for reducing switching losses and improving overall converter efficiency with help of resonant elements are discussed. In addition, control strategies for power ow control with enhanced soft switching of partly isolated converters are highlighted. A summary of converter topologies is provided comparing power rating, device count, soft switching resonant elements and efficiency which gives an idea for selection of suitable topology for the desired system requirement.